AKTIVASI PERAN BINA KELUARGA REMAJA DALAM PENGURANGAN RESIKO BENCANA BANJIR MENUJU KEMANDIRIAN BENCANA DIKAMPUNG KB PUCANGSAWIT,SURAKARTA - Dewi Kartika Sari; Rina Sri Widayati2; Yulaikha Istiqomah; Saftirta Gatra Dewantara; Sandy Anwar Mursito; Jani Kusanti (P3M Universitas Aisyiyah Surakarta, 2020)
Flood is a natural event caused by the overflowing of water out of the river channel because the volume of water exceeds the capacity of the available river channels. An area of overflow from a river is referred to as a flood-plain area. Kampung KB which is located in Pucang sawit Village, Jebres, Surakarta, is located along the side of the Bengawan Solo river, making this location prone to the impact of the overflowing of the Bengawan Solo river in this extreme weather. Therefore, disaster mitigation activities in the form of flood disaster management are needed for the people of that area. The prevalence of heavy rain in Indonesia is increasing, resulting in an increased risk of flooding. The result of this problem is the lack of public knowledge regarding how to deal with flood disasters that may arise. The solution is with disaster training in the form of activating the role of youth family development in the KB village. The target output expected from this health education is the increasing number of people who know the procedures for handling floods in disaster locations, as well as youth being able to play an active role in disaster activities. Information on the Activation of Action and the Role of Youth in Flood Disaster Management in Kampung KB Pucangsawit, Surakarta was held on the 21st October 2020, followed by five students, two accompanying lecturers and audiences. During the counseling, a demonstration of first aid was carried out in the case of floods and questions and answers to clarify the understanding of the residents. After counseling about first aid to flood victims, we also did scene designs or actions in the field and practiced what had been taught directly on the banks of the Bengawan Solo river.